Transitional housing as an inclusionary planning intervention: The pickwick transitional housing project - Siff, Enrique (School of Architecture, Planning and Geomatics, 2024)
This dissertation explores if and how transitional housing, as a state intervention, enhance the inclusion of disenfranchised residents in well-located neighbourhoods. The City has often been criticised for relocating evictees to its Temporary Relocation Areas (TRAs) on the urban edge, away from the city centres and places of employment. At least 75% of Cape Town's households continue to be excluded from accessing centrally located municipal services (Ndifuna Ukwazi, 2021), whilst ongoing evictions and displacements of hundreds of families from inner-city neighbourhoods culminate in “a systemic crisis that has been going on for over a decade” (Pillay, et al., 2017:2; also see Le Grange, 1985). In response to the ongoing housing crisis, transitional housing is increasingly being advocated for by state entities and non-government organisations (NGOs) as an alternative housing model to remedy aspects of the ever-escalating demands for affordable accommodation in Cape Town (and elsewhere in South Africa and globally). As such, this dissertation explore if and how the Pickwick Transitional Housing project meets the City's commitment and mandate to enable a more integrated and inclusive city for all. This research is explored by deploying discourse analysis and the case study methods (semistructure interviews and mapping research techniques). It focused on the Pickwick Transitional housing pilot project in Salt River, Cape Town as the case under study. It investigated a case of a group of people who had originally lived nearby in Woodstock, Cape Town, but who were ultimately forced to settle informally in the neighbourhood and had been relocated to the Pickwick facility in Salt River. Key discussions presented throughout this dissertation thus focus on: (1) the significance of transitional housing in enabling integrated and inclusive spatial planning outcomes; (2) the role of transitional housing in facilitating affordable housing options for poor and working-class residents in well-located areas; and (3) the prospects of transitional housing becoming alternative, and formal, mechanisms to remedy evictions and displacements from inner-city neighbourhoods undergoing gentrification. This research made policy recommendations for transitional housing, as well as recommendations targeted at legislation and some organisations.